Biodegradation of Polyethylene and Plastic Mixtures in Mealworms (Larvae of Tenebrio molitor) and Effects on the Gut Microbiome - Brandon, Anja Malawi; Gao, Shu-Hong; Tian, Renmao; Ning, Daliang; Yang, Shan-Shan; Zhou, Jizhong; Wu, Wei-Min; Criddle, Craig S (Environmental science & technology, 2018)
Recent studies have demonstrated the ability for polystyrene (PS) degradation within the gut of mealworms (Tenebrio molitor). To determine whether plastics may be broadly susceptible to biodegradation within mealworms, we evaluated the fate of polyethylene (PE) and mixtures (PE + PS). We find that PE biodegrades at comparable rates to PS. Mass balances indicate conversion of up 49.0 ± 1.4% of the ingested PE into a putative gas fraction (CO2). The molecular weights (M n) of egested polymer residues decreased by 40.1 ± 8.5% in PE-fed mealworms and by 12.8 ± 3.1% in PS-fed mealworms. NMR and FTIR analyses revealed chemical modifications consistent with degradation and partial oxidation of the polymer. Mixtures likewise degraded. Our results are consistent with a nonspecific degradation mechanism. Analysis of the gut microbiome by next-generation sequencing revealed two OTUs (Citrobacter sp. and Kosakonia sp.) strongly associated with both PE and PS as well as OTUs unique to each plastic. Our results suggest that adaptability of the mealworm gut microbiome enables degradation of chemically dissimilar plastics.